NAVIGATING THE COMPLEXITIES: TEACHER CHALLENGES IN ADOPTING COMMUNICATIVE LANGUAGE TEACHING STRATEGIES IN THE CONTEXT OF INDONESIAN VOCATIONAL HIGH SCHOOLS - Sampelolo, Rigel; Salu, Agustinus; Kabanga, Daniel Paberu (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
The shift toward the Merdeka Curriculum in Indonesia emphasizes communicative competence in English language learning, making the effective implementation of Communicative Language Teaching Strategies (CLTLS) increasingly urgent, especially in vocational high schools where practical language skills are essential. This study investigates the challenges faced by English teachers in implementing CLTLS within this context. Using a qualitative approach, data were collected through classroom observations, in-depth interviews with English teachers, and analysis of relevant teaching documents. The findings reveal five major challenges: (1) difficulty in adapting communicative strategies to diverse student characteristics and vocational needs; (2) low student motivation and confidence in using English communicatively; (3) limited availability of teaching materials that support communicative practices; (4) assessment systems that remain focused on grammar rather than communicative competence; and (5) lack of institutional support coupled with administrative burdens that restrict teachers’ ability to innovate. These challenges indicate that successful implementation of CLTLS in vocational schools requires systemic improvements, including curriculum adjustments, development of context-relevant materials, enhancement of student engagement strategies, and stronger institutional backing.